Internet application Mozilla localization and using in teaching - Gintautas Grigas; Tatjana Jevsikova (Lietuvos Matematikos Rinkinys)
The analysis of Intemet application Mozilla using at school is presented. The reasons to discuss this topic are following: 1) the programs' suite was localized (menu, dialog boxes and other strings and documentation are translated and the program is adapted for its proper matching to Lithuanian environment); 2) using one Mozilla package for teaching Intemet topics instead of separated Internet applications (web browser, HTML composer, e-mail and chat clients) has many advantages. The new features, added into Mozilla during its localization, are described, farther improvement possibilities are evaluated and a short curriculum is presented.